Risk Factors and Changes of Peripheral NK and T Cells in Pulmonary Interstitial Fibrosis of Patients with Rheumatoid Arthritis - Na-Lin Lai; Wen Jia; Xia Wang; Jing Luo; Guang-Ying Liu; Chong Gao; Xiao-Feng Li; Jian-Fang Xie (Canadian Respiratory Journal)
Objective. The absolute and relative changes of peripheral NK and T subsets are unclear in rheumatoid arthritis (RA) associated with pulmonary interstitial fibrosis (RA-ILD). To investigate the clinical risk factors, especially the changes of lymphocyte subsets, in RA-ILD in order to make early diagnosis and achieve prevention of the pulmonary interstitial lesions. Methods. A total of 100 RA and 100 RA-ILD patients were enrolled. Rheumatoid factor, anti-cyclic citrulline peptide antibody, erythrocyte sedimentation rate, immunoglobulin, and C-reactive protein were examined. The percentage and absolute number of NK, T, B, Treg, Th1, Th2, and Th17 cells in peripheral blood were determined by flow cytometry. Results. RA-ILD is more common in older and male RA patients and/or those with higher autoantibody titers. Flow cytometry showed that the absolute and relative numbers of CD56+ NK cells were significantly higher in RA-ILD (280.40 ± 180.51 cells/μl vs. 207.66 ± 148.57 cells/μl; 16.62 ± 8.56% vs. 12.11 ± 6.47%), whereas the proportion of T cells and CD4+ T cells was lower in peripheral blood of RA-ILD patients (69.82 ± 9.30%; 39.44 ± 9.87 cells/μl) than that in RA patients (74.45 ± 8.72%; 43.29 ± 9.10 cells/μl). Conclusions. The occurrence of RA-ILD is closely related to the older male patients with high titer of various self-antibodies. Imbalance of CD3−CD56+ NK cells and T cells with other subsets were found in RA-ILD patients, which, together with older age, male, and high levels of autoantibodies should be considered as risk factors of pulmonary interstitial lesions.